PENGARUH PENDIDIKAN, PERTUMBUHAN EKONOMI, DAN TINGKAT UPAH TERHADAP JUMLAH PENGANGGURAN DAN KEMISKINAN DI KABUPATEN KARANGASEM - Linggawati, Ni Wayan; Wenagama, I Wayan (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.11.NO.04.TAHUN.2022, 2022)
Poverty is one of the benchmarks for the success of development. At the national and regional levels, poverty is a complex and chronic problem so that appropriate and sustainable strategies are needed to overcome it. This study aims to analyze 1) the direct effect of education level, economic growth and wage levels on the number of unemployed, 2) the direct influence of education level, economic growth and wage levels on poverty, 3) The effect of education level, economic growth and wage levels on poverty in general. indirectly through the number of unemployed in Karangasem Regency. This study uses secondary data from 2006 – 2020 with quantitative and qualitative data types. The data analysis technique used is path analysis with the software used is SPSS. Based on the results of the study, it was found that the level of education, economic growth, wage levels had a direct and significant effect on the number of unemployed in Karangasem Regency. The variables of education level, economic growth, wage level have a direct and significant effect on poverty in Karangasem Regency. The variable number of unemployed is a mediating variable that indirectly influences the level of education, economic growth, wage levels on the number of poverty.